Current issues in highway design proceedings of the Conference on Highway Design, Today and Tomorrow, organized by the Institution of Civil Engineers and held in London on 6 February 1985. (Thomas Telford, 1985)
Aimed at civil engineers, these papers focus on system development and monitoring designs, landscape considerations when building motorways, provide geotechnics and topographical data, and discuss computer aided drafting in highway engineering.